Influence of a remote sulfinyl group on l-proline-catalyzed direct asymmetric aldol addition of acetone. Issue 35 (1st September 2016) - Villano, Rosaria; Acocella, Maria Rosaria; Scettri, Arrigo
Abstract: The addition of acetone to rac -2-methylsulfinyl-benzaldehyde, catalyzed by secondary amines (morpholine, piperidine, l -proline, l -prolinamide and ( S )-(–)-α, α-diphenyl-2-pyrrolidinemethanol trimethylsilyl ether), was realized. Interesting aspects, such as 1, 4-asymmetric induction by the remote sulfinyl group of the aldehyde but also the stereochemical control and kinetic resolution of the racemic substrate by the chiral organocatalyst were examined. Finally, an unexpected stereoselective retro-aldol reaction catalyzed byl -proline was pointed out. Graphical abstract: